COVID19 and acute lymphoblastic leukemias of children and adolescents: Updated recommendations (Version 2) of the Leukemia Committee of the French Society for the fight against Cancers and leukemias in children and adolescents (SFCE) - Rouger-Gaudichon, Jérémie (Bull Cancer, 2021)
Since the emergence of the SARS-CoV-2 infection, many recommendations have been made. However, the very specific nature of acute lymphoblastic leukemias and their treatment in children and adolescents led the Leukemia Committee of the French Society for the fight against Cancers and leukemias in children and adolescents (SFCE) to propose more specific recommendations. Here is the second version of these recommendations updated according to the evolution of knowledge on COVID19.